2009
DOI: 10.1007/s00198-009-0978-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover in patients with endogenous Cushing’s syndrome before and after successful treatment

Abstract: Our study demonstrated significant correlations between serum cortisol and both bone formation and resorption markers in the active phase of CS. We propose that OC may serve as a sensitive biologic marker of glucocorticoid activity in endogenous CS during its active phase and it may reflect the clinical cure of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 27 publications
4
27
0
2
Order By: Relevance
“…A high circulating cortisol concentration is both a stimulant of osteoclast activity and a suppressor of osteoblast activity, where only above a certain concentration does cortisol exert a significant resorptive effect on bone (Szappanos et al 2010). In support of the existence of a cortisol threshold, the current study found a significant positive correlation between serum cortisol concentration and serum ␤-CTX concentration on day 1 postexercise, which also corresponded to the highest cortisol response, and no correlation on days 2 to 4 postexercise where a lower postexercise cortisol concentration was recorded.…”
Section: B † † †mentioning
confidence: 99%
See 1 more Smart Citation
“…A high circulating cortisol concentration is both a stimulant of osteoclast activity and a suppressor of osteoblast activity, where only above a certain concentration does cortisol exert a significant resorptive effect on bone (Szappanos et al 2010). In support of the existence of a cortisol threshold, the current study found a significant positive correlation between serum cortisol concentration and serum ␤-CTX concentration on day 1 postexercise, which also corresponded to the highest cortisol response, and no correlation on days 2 to 4 postexercise where a lower postexercise cortisol concentration was recorded.…”
Section: B † † †mentioning
confidence: 99%
“…Moreover, cortisol is known to influence bone metabolism (Szappanos et al 2010). For instance, an increase in serum cortisol concentration following an ultra-marathon run was negatively correlated to bone formation markers (Mouzopoulos et al 2007), thus implicating cortisol and possibly metabolic stress as manipulates of exercise-associated bone turnover disruption.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Nevertheless, many researchers have demonstrated a statistically significant reduction in OC levels in patients receiving glucocorticoid therapy 12,13 and in patients with endogenous hypercortisolism. [14][15][16] The resulting suppression of bone formation is so profound that OC levels were tested and shown to be effective in differentiating endogenous Cushing's syndrome (CS) from healthy control subjects with an area under the curve (AUC) of 0.922, which is similar to the late-night salivary cortisol (LNSC) of 0.994 obtained from a receiver operating characteristic (ROC) analysis in the same cohort of people. 17 However, the most challenging cases involve differentiating patients with endogenous CS from obese subjects due to similar clinical features and complications such as the presence of functional hypercortisolism with relatively higher cortisol levels in obese subjects compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Due to increased protein catabolism and negative nitrogen balance, muscular atrophy, osteoporosis and fragility of connective tissue are often encountered. Levels of free fatty acids and cholesterol are increased in plasma, and a centripetal distribution of fatty tissue is characteristic [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%